DIGITAL INDIA AND ICT INTEGRATION IN BANKING: A COMPARATIVE ASSESSMENT OF CUSTOMER SATISFACTION AND PERFORMANCE IN PUBLIC AND PRIVATE SECTOR BANKS OF PUNJAB - Khanna, Bala; Sood, Sarita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The current research focuses on the levels of customer satisfaction and effectiveness related to digital banking services of public and private bank sector were taken into study with the comparative perspective on consumers preferences and demographics impact and institutional performance as well. Based on empirical evidence of the 100 respondents and using secondary financial reports of 100 respondents data from 2010 to 2020, descriptive statistics, chi square testing, and t test were applied to examine the behavioral pattern and performance parameters including ROCE, ROA and Net Profit margin. The results demonstrate a solid preference for digital services, over manual services in the private sector, leading to a significant improvement in the satisfaction of customers and speed of service among various demographics. Moreover, private banks have fared better than public banks in terms of profitability and digital adoption. The study emphasizes the imperative for public sector banks to step up their digital game in a bid to enhance customer experience and increase financial inclusion through customer-friendly digital banking services.